2021
DOI: 10.3390/educsci11100640
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Using Socio-Scientific Issues and Technology in Problem-Based Learning: A Systematic Review

Abstract: Currently, a growing number of learning institutions at all educational levels are including problem-based learning (PBL) in their curricula. PBL scenarios often utilise technology and socio-scientific Issues (SSI), which enables the simultaneous learning of content and creative thinking and working skills needed in generating new knowledge for the future. In this sense, using SSI and technological tools in PBL learning environments can be viewed as a starting point for acquiring and integrating new knowledge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 90 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…From the perspective of constructive learning theory, teachers were more aware of the students' demand for teaching materials. Therefore, this study found that the PBL approach offered great potential in supporting real-world problem solving of AI contextual ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/ issues in science education (Hernández-Ramos et al, 2021). As mentioned above, Rillero and Chen (2019) found that PBL could combine diverse AI subjects with meaningful experiences for authentic learning outcomes.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…From the perspective of constructive learning theory, teachers were more aware of the students' demand for teaching materials. Therefore, this study found that the PBL approach offered great potential in supporting real-world problem solving of AI contextual ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/ issues in science education (Hernández-Ramos et al, 2021). As mentioned above, Rillero and Chen (2019) found that PBL could combine diverse AI subjects with meaningful experiences for authentic learning outcomes.…”
Section: Discussionmentioning
confidence: 74%
“…Rillero and Chen (2019) also found that PBL could combine different curriculum themes with meaningful experiences. In addition, Hernández-Ramos et al (2021) emphasized that the PBL approach offered learning potential in addressing real environmental problems in natural science education. Accordingly, this research used the PBL teaching method and designed the life teaching situation of AI application in society as the issue of classroom discussion.…”
Section: Application Of Pblmentioning
confidence: 99%
“…Sadler (2004) conducted a comprehensive review of informal reasoning research in the context of SSI, encompassing four aspects: social scientific argumentation, the relationship between scientific nature conceptualization and decision-making, the evaluation of SSI source information, and the impact of a conceptual understanding on informal reasoning [1]. Hernandez-Ramos and colleagues conducted a review of the use of SSI in problem-based learning [23]. Researchers from South Korea utilized the program analysis framework [24] to analyze SSI education research in their country from 2000 to 2016 [25].…”
Section: Literature Review Of Ssi Education Researchmentioning
confidence: 99%
“…In addition, ICTs have offered different advantages, among which the following stand out (Noghabaei et al., 2020): (i) greater automation and optimisation of processes; (ii) the creation of different virtual teaching environments and methods; (iii) rapid and unlimited access to information and resources; and (iv) a greater capacity to model and simulate processes, systems and projects. In scientific disciplines, there are many challenges and opportunities offered by ICT, including the development of ICT‐based resources, as well as the development in teachers of the digital competencies necessary for the use of ICT (Hernández‐Ramos et al., 2021).…”
Section: Literature Reviewmentioning
confidence: 99%